Uncertainty and non-linear macroeconomic effects of fiscal policy in the US: A SEIVAR-based analysis - Ansgar Belke; Pascal Goemans (RWI - Leibniz-Institut für Wirtschaftsforschung, 2019)
We investigate whether the macroeconomic effects of government spending shocks vary with the level of uncertainty. Using postwar US data and a Self-Exciting Interacted VAR (SEIVAR) model, we find that fiscal spending has positive output effects in tranquil times but is contractionary during uncertain times. The endogenous reaction of macroeconomic uncertainty plays an important role in explaining the non-linear impact of government spending. In contrast to other types of government spending, research and development expenditures reduce uncertainty and have an expansionary effect on output during uncertain times. – – Die Studie untersucht, ob die gesamtwirtschaftlichen Auswirkungen unerwarteter Staatsausgabenerhöhungen mit dem vorherrschenden Grad an Unsicherheit in einer Volkswirtschaft zusammenhängen. Anhand von US Nachkriegsdaten und einem SEIVAR finden wir positive Effekte auf die Wirtschaftsleistung in Zeiten niedriger Unsicherheit und negative Effekte in Zeiten sehr hoher Unsicherheit. Die endogene Reaktion der gesamtwirtschaftlichen Unsicherheit stellt einen wichtigen Faktor für die Erklärung der nichtlinearen Auswirkungen der Staatsausgaben dar. Die Ergebnisse zeigen zudem eine Abhängigkeit der Effekte von der Art der Staatsausgaben. Im Gegensatz zu anderen Arten von Staatsausgaben reduzieren Forschungs- und Entwicklungsausgaben den Grad gesamtwirtschaftlicher Unsicherheit und wirken in unsicheren Zeiten expansiv auf die Wirtschaftsleistung.
Keywords: E62; E32; C32; 330; Government spending shocks; uncertainty; non-linear structural vector autoregressions; interacted VAR; generalized impulse response functions; endogenous uncertainty